Pengaruh Media Digital, Pengembangan Karir Dan Pelatihan Kerja Terhadap Kualitas Pelayanan Kepada Masyarakat di Kantor BPJS - Lubis, Muhammad Taufan Rizka; Anshar, Teuku; Winatha, Muhammad Dede; Kurniawan, Hadi; Supriadi, Supriadi; Helmi, T. Ahmad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This research was conducted with the aim of determining the influence of job training variables on the quality of service to the community at the BPJS Health Langsa Branch Office. The research was conducted using a quantitative approach. The research technique used distributing questionnaires (Likert scale questionnaires) to 46 research respondents. The research results show that: 1) Digital media has a negative and insignificant effect on the quality of service to the community at the BPJS Health Langsa Branch office. The results of this research are based on the coefficient value tcount < ttable, namely - 1,730 < 1.680 with a significance of 0.091 > 0.05. It was concluded that the research hypothesis H₀ was accepted and H1 was rejected. This means that there is no influence between digital media on the quality of service at the Langsa Branch BPJS Health Office. 2) Career development has a positive and significant effect on the quality of service to the community at the Langsa Branch BPJS Health Office. The results of this research are based on the coefficient value tcount > ttable, namely 19,697 > 1.680 with a significance of 0.000 < 0.05. It was concluded that the research hypothesis H0 was rejected and H2 was accepted. This means that there is an influence between development on the quality of service at the Langsa Branch BPJS Health Office, 3) Job training has a positive and significant effect on the quality of service to the community at the Langsa Branch BPJS Health Office. The results of this research are based on the coefficient value tcount < ttable, namely 4,355 > 1.680 with a significance of 0.000 > 0.05. It was concluded that the research hypothesis H0 was rejected and H3 was accepted. This means that there is an influence between job training on the quality of service at the Langsa Branch BPJS Health Office. 4) Digital media, career development and job training simultaneously or together have a positive effect on the quality of service to the community at the Langsa Branch BPJS Health Office. The results of this research can be seen from Digital Media (X1), Career Development (X2), Job Training (X3) with a significant value of α 0.000 < 0.05 and a value of Fcount > Ftable (972,032 > 3.21). Based on the ANOVA table, the significance level used is 0.05. Thus, the decision is obtained that H0 is rejected and H4 is accepted. Therefore, this research is suitable to be used because the independent variable has a positive effect on the dependent variable.